2015
DOI: 10.3389/fnins.2015.00117
|View full text |Cite
|
Sign up to set email alerts
|

The role of the autonomic nervous system in Tourette Syndrome

Abstract: Tourette Syndrome (TS) is a neurodevelopmental disorder, consisting of multiple involuntary movements (motor tics) and one or more vocal (phonic) tics. It affects up to one percent of children worldwide, of whom about one third continue to experience symptoms into adulthood. The central neural mechanisms of tic generation are not clearly understood, however recent neuroimaging investigations suggest impaired cortico-striato-thalamo-cortical activity during motor control. In the current manuscript, we will tack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 45 publications
0
26
1
Order By: Relevance
“…However, the ACC has been associated with many processes (see http://neurosynth.org/analyses/terms/acc/) and, therefore, its role in modulating PNS function is unlikely to be specific [Yarkoni et al, ]. Subcortical brain regions are also implicated in modulating PNS function, and the amygdala and pallidum have both previously been associated with core parasympathetic tone, albeit for disparate autonomic functions including metabolism, reward, emotion and motor response [Allen et al, ; Critchley, ; Critchley and Harrison, ; Hawksley et al, ; Macefield, ; McDougall et al, ; Novac and Bota, ; Park and Thayer, ; Su et al, ; Tanaka et al, ]. We have demonstrated that the amygdala and pallidum differ in shape depending on an individual's resting CVT.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ACC has been associated with many processes (see http://neurosynth.org/analyses/terms/acc/) and, therefore, its role in modulating PNS function is unlikely to be specific [Yarkoni et al, ]. Subcortical brain regions are also implicated in modulating PNS function, and the amygdala and pallidum have both previously been associated with core parasympathetic tone, albeit for disparate autonomic functions including metabolism, reward, emotion and motor response [Allen et al, ; Critchley, ; Critchley and Harrison, ; Hawksley et al, ; Macefield, ; McDougall et al, ; Novac and Bota, ; Park and Thayer, ; Su et al, ; Tanaka et al, ]. We have demonstrated that the amygdala and pallidum differ in shape depending on an individual's resting CVT.…”
Section: Discussionmentioning
confidence: 99%
“…83 Thus, the pathophysiology of tic fluctuations may comprise of a dopaminergic modulation of the basic impairment of the CBG loop. Another line of evidence links the modulation of tics with different states of arousal, leading the idea that tics can be suppressed by reducing sympathetic autonomic arousal, 84,85 which is regulated by the noradrenergic system. 86 Along these lines, both a2 noradrenergic agonists and the D2 dopaminergic antagonist are used to treat motor tics.…”
Section: Behavioral Statesmentioning
confidence: 99%
“…Autonomic modulation might therefore have an influence on CNS function and tic occurrence. 44 Neurofeedback is a noninvasive method of autonomic modulation that is based on operant conditioning. It displays real-time physiologic processes such as brain activity, heart rate, or electrodermal activity and by using relevant feedback directs patients how to modulate their physiologic responses.…”
Section: The Futurementioning
confidence: 99%